Gender Differences in Medication Adverse Effects Experienced by People Living With Chronic Pain - Nguena Nguefack, Hermine Lore; Gabrielle Pagé, M.; Guénette, Line; Blais, Lucie; Diallo, Mamadou; Godbout-Parent, Marimée; Angarita-Fonseca, Adriana; Lacasse, Anaïs (Frontiers in Pain Research, 2022)
Objectives: Understanding gender differences in chronic pain (CP) outcome research is essential to optimal treatment delivery. This study explored the associations between gender identity, gender roles, and the number of non-life-threatening pain medication adverse effects reported as severe by people living with CP. Methods: The analyses were conducted using the COPE Cohort, a dataset generated through a web-based recruitment of adults with CP. Participants were asked how they identified themselves (women, men, unknown, unspecified) and gender roles were measured using the Bem Sex-Role Inventory (subgroups were formed applying the median split method). Pain medication adverse effects were assessed using a standardized checklist (none/mild/moderate/severe). A zero-inflated Poisson model was used to assess gender identity, gender roles and their interaction as potential predictors of the number of pain medication adverse effects. Results: A total of 1,343 participants reported using pain medications. Adjusting for potential confounders, both gender identity (men vs. women: ß = -0.32, p = 0.0024) and gender roles (androgynous vs. undifferentiated: ß = 0.26, p = 0.0030) were associated with the number of pain medication adverse effects reported as severe, and they interacted with each other. The stratified analysis by gender roles showed that women reported a greater number of severe adverse effects than men among those classified as masculine and androgynous. Discussion: Although we are unable to confirm whether the associations can be explained by differences in the experience or in the reporting of effects, gender identity and gender roles should both be explored when studying pain medication adverse effects.